Over prescription of Proton Pump Inhibitors on discharge of Medical Inpatients - Biswas, Sarmistha; Sufian, ABM Abu; Sarkar, Prodip Kumar; Chowdhury, Mostofa Kamal; Chowdhury, Joybaer Anam; Bala, Chandra Shekhar; Islam, Md Rafiqul; Ahasan, HAM Nazmul; Kashem, MA (Journal of Medicine, 2017)
Background: Proton pump inhibitors (PPIs) are the drugs used to treat and prevent acid peptic conditions. Their efficacy and safety profile has led to injudicious prescription of these drugs exposing patients to various potential risks and increased healthcare expenditure. Methodology: A retrospective observational study was done from 10th January to 24th January, 2015 in Medicine Indoor in a tertiary care hospital to determine the trend of prescribing PPIs on discharge of Medical inpatients. Result: We found 117 patients were discharged in the study period; 83 were male and 34 were female. Among them 102 (87.17%) were prescribed PPIs on their discharge. Mean age was 44.79 years. Among the study population only 29 patients (28.5%) truly needed PPIs during their discharge. The mean duration of prescribed PPIs was 28 days. Conclusion: Amore rational prescription of PPI during discharge will have better impact on patient safety and health care expenditure. J MEDICINE January 2017; 18 (1) : 27-29